Penatalaksanaan Terapi Latihan Post Operasi Malunion Fraktur Patella Sinistra Di Rso Prof. Dr. Soeharso Surakarta - Rifai, Mahardika Agung, Yulisna Mutia Sari, MSc (GRS) (2015)
Backgund: Fracture is often called broken bone is a breakage of bone network continuity and, or easily broken bone that is caused by bone porous illness that is familiar called osteoporosis. It usually attacks adult people and also can be caused by accident. Fracture patella is often considered unimportant by some people. If it is not handled well, therefore it can cause bones join uncorrectly/imperfectly Malunion. Goal: To know the realization of physiotherapy in decreasing pain. To increase the scope of joint movement, increase the strength of muscles, decrease Odema, decrease spasm, decrease contracture and increase the daily functional activity on a case of Malunion Fracture patella Sinistra by training therapy modality ( Stastic contraction, active movement, passive movement, stretching, hold relaxed ). Result: After the therapy is done for six times, it is gotten the decressive results of pain. The increase muscle strength of thigh. The decrease of oedema on ankle and the increase of joint movement scope on hip, knee, and ankle. Conclusion: Training therapy (Static contraction, active movement, passive movement, stretching, hold released) decrease pain, Odema, increase the strength of muscle, and the scope of joint movement. On a case of Malunion fracture patella sinistra. Keywords: Malunion, Fracture, Patella